Born Fat: The Relations Between Weight Changeability Beliefs and Health Behaviors and Physical Health. (June 2016) - Parent, Mike C.; Alquist, Jessica L.
Although some popular press and nonscholarly sources have claimed that weight is largely unchangeable, the relationship between this belief and objective measures of health remains unclear. We tested the hypothesis that people who believe weight is unchangeable will have poorer objective and subjective health, and fewer exercise behaviors and poorer eating habits, than people who believe weight is changeable. Participants were 4, 166 men and 4, 655 women enrolled in the National Health and Nutrition Examination Survey in the 2007 to 2010 iterations. Believing that weight was uncontrollable was negatively related to exercise and healthful dietary practices and positively related to unhealthful eating. Lack of exercise and unhealthful eating were, in turn, associated with poor physical health. Age, but not gender, moderated the relationships between belief in weight changeability and exercise behaviors, healthful eating, and unhealthful eating. This study suggests that believing weight is unchangeable is associated with poor health behaviors and poorer physical health.